Peranan Guru Pendidikan Agama Islam dalam Menanggulangi Kenakalan Siswa - Hasikin, Nurul; Wiza, Rahmi; Nurjanah, Nurjanah (Prodi Pendidikan Keagamaan Islam, 2022)
This research is motivated by the community's view of the school which was initially famous for naughty children, then over time, this school has increasingly experienced an increase in a better direction. This study aims to determine the causes of student delinquency and the role of Islamic Religious Education teachers in tackling student delinquency. This type of research is qualitative with the case study method. (Nazir, 2003) said this case study research aims to study and understand a specific case, wherein the early stages of research it is equipped with a theoretical framework with the analysis in the form of one person, one organization, or a case and the researcher acts as an observer who analyzes why and how. of a case. Data collection techniques using interviews, observation, and documentation. The data that has been collected is then analyzed by data reduction, data presentation, and drawing conclusions. The validation of the data in this study used source triangulation, in which the researcher compared several informants in order to obtain valid data. The results showed that student delinquency that occurred at SMPN 9 Payakumbuh City was still classified as moderate delinquency, such as smoking, skipping school without explanation, fighting, saying rude and being disrespectful to the teacher.